DEVELOPING STUDENTS’ SOCIAL ACTIVITY THROUGH INTERACTIVE METHODS (BASED ON ROLE-PLAYING GAMES AND PROBLEM SITUATIONS) - Napasova Sitora (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article analyzes the theoretical and pedagogical foundations of developing students’ social activity through interactive teaching methods. The study scientifically substantiates the impact of interactive educational technologies based on role-playing games and problem situations on students’ communicative competence, social adaptation, collaborative activity, and critical thinking skills. In addition, the pedagogical possibilities of interactive methods in shaping students as active participants in the educational process are revealed. The article also highlights the importance of competency-based and student-centered approaches in improving the effectiveness of modern education.